Pengaruh Keberagaman Berdasarkan Gender, Keterampilan Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan - Harianja, Michael Abed Nego; Setiawan, Alan; Viery, Amal; Keane, Steven (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to identify Diversity based on gender, work skills, and work motivation on employee performance in the city of Palembang. The study was conducted using a quantitative approach, through a survey with a questionnaire to employees in the city of Palembang. The analysis methods used include descriptive analysis, classical assumption tests, multiple linear regression, and hypothesis testing. The results of the study indicate that gender, work skills, and work motivation have a significant effect on employee performance in the city of Palembang. Gender diversity contributes to increased creativity and problem solving, relevant work skills increase task efficiency, while work motivation encourages employee commitment and dedication. These findings provide important implications for organizations in designing more effective human resource management strategies. The F test shows that simultaneously, the three variables significantly affect employee performance in the city of Palembang. Partially, the t test reveals that gender diversity, work skills, and work motivation have a positive effect on employee performance in the city of Palembang.